Potensi pemanfaatan pektin sabut kelapa dalam pengusahaan perkebunan kelapa=Potential Usage of Coconut Husk Pectin in Integrated Plantation and Coconut Industry - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1988)
ABSTRACT Coconut husk is a considerable portion of the waste in the processing of coconut fruit. It contains some pectin which might be useful to support pectins based food industry. No information available yet on the functional properties as welt as its extractibility of the husk pectin. This study tried to explore those information. The coconut husk is extracted its pectin by the processes of extraction, precipitation, purification and drying, in order to determine the extraction recovery. To determine potential usage of extracted coconut husk pectin, its properties is compared with apple pomace pectin. The extractable pectin 1,67% with metlwayl and polyuronide contents 8.19% and 74,1%, respectively and molecular weight is 152,360. Based on the amount of =tradable pectin and its functional properties, the coconut husk pectin has poten